1984
DOI: 10.1113/expphysiol.1984.sp002777
|View full text |Cite
|
Sign up to set email alerts
|

Peristalsis and Antiperistalsis in the Chicken Caecum Are Myogenic

Abstract: SUMMARYPeristalsis in the chicken caecum was investigated by recording the responses of isolated segments of the caecum to either fluid distension using a modified Trendelenburg apparatus or by monitoring circular muscle activity following localized radial distension of adjacent areas.Raising the intraluminal pressure did not initiate peristalsis except in the presence of tetrodotoxin, local anaesthetics and high concentrations of phentolamine. The effect of these drugs was reversible. Localized distension gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…13 A weakness in the EAS will then cause urge or evacuation. The exact effect of the contractions of different parts of EAS and other structures surrounding the anal canal needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…13 A weakness in the EAS will then cause urge or evacuation. The exact effect of the contractions of different parts of EAS and other structures surrounding the anal canal needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, since peristalsis in the chicken gut is myogenic (Bartlet, 1973;Mizuta et al 1980;Hodgkiss, 1984a), in order for peristalsis to occur some mechanism must exist to release the intestinal smooth muscle from the influence of enteric inhibitory neurones, which are known to be present (Bartlet, 1973;Hodgkiss, 1984a).…”
Section: Discussionmentioning
confidence: 99%
“…Our in vivo study showed a significant increase of the lactate-producing species Lactobacillus crispatus in the colon and the lactate-utilizing butyrate-producing species Anaerostipes butyraticus in the cecum. The lactic acid produced by L. crispatus in the colon may reach the cecum and become available for A. butyraticus due to antiperistalsis (55,56). The in vitro fermentation assay showed that reference strains of both species metabolized XOS, resulting in production of high concentrations of lactic acid by L. crispatus, which were thought to be consumed by the butyrate-producing bacterium A. butyraticus.…”
Section: Discussionmentioning
confidence: 99%